The impact of teaching and learning quality process to school and university education for sustainable future - Louisa Marga Metekohy; Muner Daliman; Benjamin Metekohy; David Ming (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The purposes of this study are: 1) To determine the effect of the quality of the learning process and learning motivation on student achievement partially. 2) To determine the effect of learning motivation on student achievement. This research design is a qualitative research, with a grounded theory type of research.The impact of the teaching and learning quality process affects the improvement of student learning outcomes in addition to the selection of inputs, there are also other factors that determine the so-called external factors and students' internal factors. External factors of students include school infrastructure, teachers, learning processes and other factors that come from the family environment. While internal factors, including health, intelligence, talent, interests, motivation and so on. The influence of the quality of the learning process is a very important factor in determining student learning outcomes. Meanwhile, motivation is a factor to generate, underlie, and direct students' learning actions. The conclusion in this study is that the aspect that is the determining factor for obtaining satisfactory achievement for students in learning is friends who will affect student achievement. The surrounding environment can motivate children to learn if it consists of students, students, doctors. This activity in the community can also affect children's learning.